2016
DOI: 10.1039/c6dt02961b
|View full text |Cite
|
Sign up to set email alerts
|

Improving selectivity in catalytic hydrodefluorination by limiting SNV reactivity

Abstract: Catalytic hydrodefluorination of perfluoroallylbenzene with CpTiH in THF is unselective and yields a variety of previously unknown compounds, predominantly activated in the allylic position. Several different mechanisms have been examined in detail using solvent corrected (THF) DFT(M06-2X) calculations for the archetypal perfluorinated olefin perfluoropropene and perfluoroallylbenzene: (a) single electron transfer, (b) hydrometallation/fluoride elimination, (c) σ-bond metathesis (allylic or vinylic), and (d) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Final single-point energies were calculated at the M06-2X level of theory employing triple-ζ Dunning (TZ) basis sets (cc-pVTZ quality) . In addition to main-group-metal chemistry, , we found that this protocol accurately reproduces different experimental problems concerning d 0 and d 1 early-transition-metal systems in olefin polymerization (including Ti–C homolysis) ,,, and Ti­(III) chemistry. An additional cross-check on system 1′-Ph showed that results using the ωB97xd functional produced similar results. In the case of the 1′-Ph ion pair with B­(C 6 F 5 ) 4 – , only a single structure was optimized for the doublet species and the INS TS, and the given ΔΔ G ⧧ HOM‑INS value (see the Supporting Information) can likely be regarded only as an upper limit.…”
Section: Methodsmentioning
confidence: 99%
“…Final single-point energies were calculated at the M06-2X level of theory employing triple-ζ Dunning (TZ) basis sets (cc-pVTZ quality) . In addition to main-group-metal chemistry, , we found that this protocol accurately reproduces different experimental problems concerning d 0 and d 1 early-transition-metal systems in olefin polymerization (including Ti–C homolysis) ,,, and Ti­(III) chemistry. An additional cross-check on system 1′-Ph showed that results using the ωB97xd functional produced similar results. In the case of the 1′-Ph ion pair with B­(C 6 F 5 ) 4 – , only a single structure was optimized for the doublet species and the INS TS, and the given ΔΔ G ⧧ HOM‑INS value (see the Supporting Information) can likely be regarded only as an upper limit.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we have demonstrated that the choice of solvent can influence the selectivity in HDF reactions . Nonpolar solvents disfavor charge delocalization, which increases S N V barrier heights, thereby increasing selectivity.…”
Section: Resultsmentioning
confidence: 91%
“…HDF via the aluminum hydride monomer 1M proceeds preferentially via a hydrometallation–elimination sequence associated with high barriers (40–48 kcal mol −1 , when the dimerization equilibrium is factored in and predominantly enthalpic). Hydrometallation is rate limiting but elimination is selectivity determining and would yield the thermodynamically most stable Z ‐isomer 3 a in high selectivity; as all elimination TS's are energetically early but geometrically late their relative energy differences reflect those found in the products, very similar to HDF using Cp 2 TiH …”
Section: Resultsmentioning
confidence: 99%
“…However, as olefin coordination is not favored (see below), such a pathway is less likely. On the other hand, chloride attack at an olefin after silane coordination at the surface would also result in an S N V type mechanism, [34] but at least tertiary silanes show typically silylium ion type reactivity [7e,f,22b] …”
Section: Resultsmentioning
confidence: 99%